Application of ultrasound-guided radial artery puncture and catheterization in critically ill patients in the ICU (超声引导下桡动脉穿刺置管在ICU重症患者中的应用) - TONG Lu (佟璐); LIU Ai (刘爱); YAN Hong (颜红); FENG Ying (冯莹); ZHAO Zitong (赵紫彤); LI Ruiqi (李瑞祺) (中西医结合护理)
Objective To evaluate the application of ultrasound-guided radial artery puncture and catheterization in critically ill patients in the ICU. Methods Totally 40 critically ill patients undergoing radial artery puncture and catheterization were divided into the control group and study group, with 40 cases in each group. The control group adopted conventional blind puncture method, while the experimental group used bedside B-mode ultrasound-guided radial artery puncture. The one-time success rate of puncture, puncture times and the total time of puncture were recorded and compared between two groups. Results The one-time success rate of puncture was 85. 00%(17/20)in the study group, which was significantly higher than 50. 00%(10/20)in the control group (P＜0. 05). The averaged puncture times and the total time of puncture in the study group were lower than those in the control group (P＜0. 01). Conclusion The ultrasound-guided radial artery puncture and catheterization can improve the success rate of one-time puncture, shorten the puncture time and reduce the number of puncture in ICU patients. (目的 探讨超声引导下桡动脉穿刺置管在ICU重症患者中的应用效果。方法 选择40例ICU重症患者为研究对象, 穿刺部位均为桡动脉。将患者分成两组, 对照组采用常规直接触摸动脉盲穿置管法, 研究组采用床旁B型超声引导下动脉穿刺置管法。记录两组患者一次穿刺成功率、穿刺次数及穿刺时间。结果 研究组一次穿刺置管成功率85. 00%(17/20), 高于对照组的50. 00%(10/20), 差异有统计学意义(P＜0. 05)。研究组平均穿刺次数和一次穿刺平均所需时间均低于对照组, 差异有统计学意义(P＜0. 01)。结论 针对ICU重症患者在超声引导下开展动脉穿刺, 能够提高一次性穿刺成功率, 缩短穿刺时间。)